2020
DOI: 10.1002/ecs2.3097
|View full text |Cite
|
Sign up to set email alerts
|

Assessing conservation conflict: Does intertidal oyster aquaculture inhibit foraging behavior of migratory shorebirds?

Abstract: 2020. Assessing conservation conflict: Does intertidal oyster aquaculture inhibit foraging behavior of migratory shorebirds? Ecosphere 11(5):Abstract. Conservation is increasingly in conflict with human activities due to global human population

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In some cases, shorebirds, including oystercatchers and curlews, occurred in significantly lower numbers in areas with oyster racks when other suitable foraging habitats were nearby (Hilgerloh et al 2001; Burger & Niles 2017). However, there are also studies that found no significant effect of the presence of untended aquaculture structures, while tending the oyster cultivation structures by oyster farmers reduced the probability of shorebird presence (Maslo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, shorebirds, including oystercatchers and curlews, occurred in significantly lower numbers in areas with oyster racks when other suitable foraging habitats were nearby (Hilgerloh et al 2001; Burger & Niles 2017). However, there are also studies that found no significant effect of the presence of untended aquaculture structures, while tending the oyster cultivation structures by oyster farmers reduced the probability of shorebird presence (Maslo et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced visibility may ultimately cause foraging birds, which are cautious by nature, to avoid mussel beds that have been restored with the help of artificial structures, and thereby not comply with the original aims set for intertidal mussel bed restoration. While the effect of structures on bird behavior has not been studied much from a restoration perspective, studies have been conducted on the effect of intertidal aquaculture operations, such as the use of oyster culture racks or oyster longlines, on shorebirds (Connolly & Colwell 2005; Maslo et al 2020). Some of these studies have shown that shorebird species increased foraging around these aquaculture structures (Hilgerloh et al 2001; Connolly & Colwell 2005), while other studies showed that the presence of oyster culture structures did not influence habitat use and feeding rates (Maslo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the Dutch Wadden Sea, Waser et al (2016) conclude that, whilst the impacts of M. gigas are substantial, it is likely that the disturbance resulting from efforts to remove or limit the spread M. gigas would do substantially more harm than good to the avian diversity of the area. Research on the utilisation of intertidal habitats by foraging shorebirds in Delaware Bay (USA) suggests that the feeding rates are unaffected by the presence of oyster aquaculture (Maslo et al, 2020).…”
Section: Effects On Birdsmentioning
confidence: 99%
“…Reduced visibility may ultimately cause foraging birds, which are cautious by nature, to avoid mussel beds that have been restored with the help of artificial structures, and thereby not comply with the original aims set for intertidal mussel bed restoration. While the effect of structures on bird behavior has not much been studied form a restoration perspective, studies have been conducted on the effect of intertidal aquaculture operations, such as the use of oyster culture racks or oyster longlines, on shorebird (Connolly & Colwell, 2005;Maslo et al, 2020). Some of these studies have shown that shorebird species increased foraging around these aquaculture structures (Hilgerloh et al, 2001;Connolly & Colwell, 2005), while other studies showed that the presence of oyster culture structures did not influence habitat use and feeding rates (Maslo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%